THE ISSUES OF THE MODERN ERGONOMICS: THE STRUCTURAL RELIABILITY DEFINITION: Array - Protasenko, O.; Mygal, G. (Municipal economy of cities. Series: «Economy science», 2019)
Nowadays ergonomics is in a transitional state caused by factors such as the rapid transition of ergonomic systems to digital and virtual technologies, the emergence of new activities for the research and analysis of which existing tools and methods are not enough. The way out of this situation is the gradual revision and rethinking of the existing definitions and concepts of the ergonomics taking into account the requirements of modern ergonomic systems, giving them a new actual meaning. Among the basic concepts, that require primary revision, is the concept "the operator's structural reliability". In recent years, the concept of the operator's reliability was levelled due to the shift of emphasis in the study and analysis of the ergonomic systems towards certain indicators of the operator's psychophysiological state such as fatigue, stress tolerance, tension, and others. However, this did not produce the expected results in improving the safety and quality of the ergonomic systems. Structural reliability assesses a human ability to withstand the load for a given time in certain operating conditions. However, it is difficult to estimate the operator's structural reliability in condition, when the operator works on a distance, so it is reasonable to look for new methods and means of research and analysis. It was done an information search and systematization of data about the basic components of structural reliability with a purpose of update the content of the concept "the operator's structural reliability". Analytical review of information on this issue allowed us to identify three groups of the operator's structural reliability components: natural, individual, and working factors. Data systematization on the components of the operator's structural reliability identified the problematic issues which are typical to each component at this stage of the ergonomic systems development. For the “work factors” component a problematic issue is finding and developing effective means and methods of remote assisting the employee in matters of providing own safety during the activity. An initial solution to this problem is to involve resources available at the enterprise or organization, namely: the labor protection service or the employee who is responsible for the labor protection. They can provide initial counseling for the workers who work in a distance. For the component "individual factors" the problematic issue is the remote tracking of psychophysiological indicators of the operator functional state. At a primary stage to solve the problem, an annual supervised medical examination can be organized for workers who work on the distance. The problem issue of "natural factors" is the choice of indicators of the operator functional state that will identify the influence of natural factors on him. A possible solution to this problem is the use of controlled systematic medical examinations and preventive measures as in the group of "individual factors".